Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

if cose theta – cot theta =p then cosec + cot theta

if cose theta – cot theta =p then cosec + cot theta 

Grade:12th pass

2 Answers

Saurabh Koranglekar
askIITians Faculty 10341 Points
one year ago
Dear student

Cosec(x) sq - cot ( x) sq = 1

By identity

So answer of required expression is (1/p)

Regards
Arun
25763 Points
one year ago
Dear student
 
As we know
 
Cosec²x - cot²x = 1
(Cosecx - cotx) (cosec x + cotx) = 1
 
Hence (cosecx + cotx) = 1 /( cosecx - cotx) = 1/p
 
Hope it helps

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free